Persepsi Peternak Ayam Petelur terhadap Pelayanan Kredit Usaha di Bank Nagari Kecamatan Lintau Buo Utara Kabupaten Tanah Datar - Dewi, Novia; Novian, Novian; Nastiana, Dea Aulia (Universitas Galuh, 2025)
The banking sector distributes agricultural credit programs, namely KUR, which are given to laying hen breeders. One of the factors that determine the level of success and quality of the company is the company's ability to provide quality service to its customers so that there are no complaints about the services provided by bank employees. This study aims to analyze the perceptions of farmers on KUR people's business credit services at Bank Nagari Lintau Buo Utara, Tanah Datar Regency. The population in this study were all customers of laying ayan farmers with a total of 32 people. Data analysis using descriptive analysis, to determine the level of perceptions and expectations is a Cartesian diagram while the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) is to determine the level of customer satisfaction with services at Bank Nagari. The results showed that perceptions and expectations using cartesian diagrams and the Customer Satisfaction Index (CSI) method of farmers towards KUR services were classified as very satisfied, namely 89.55% related to the five variables studied, namely physical evidence (tangibles), reliability (reliability), responsiveness (responsive). assurance, and care (empathy). While the Importance Performance Analysis (IPA) method needs to be improved because there is still 10.45% unmet satisfaction found in quadrant I, namely, laying hen farmers have high expectations while satisfaction is low.